A Solid-in-Oil Nanodispersion System for Transcutaneous Immunotherapy of Cow's Milk Allergies - Momoko Kitaoka; Wei Xiao; Qingliang Kong; Yoshiro Tahara; Noriho Kamiya; Masahiro Goto (MDPI AG, 2020)
An allergy to cow’s milk proteins is the most common food allergy in infants and toddlers. Conventional oral immunotherapy for cow’s milk allergies requires hospital admission due to the risk of severe allergic reactions, including anaphylaxis. Therefore, a simpler and safer immunotherapeutic method is desirable. We examined transcutaneous immunotherapy with a solid-in-oil (S/O) system. In the S/O system, nano-sized particles of proteins are dispersed in an oil-vehicle with the assistance of nonionic surfactants. In the present study, the S/O system enhanced the skin permeation of the allergen molecule β-lactoglobulin (BLG), as compared with a control PBS solution. The patches containing BLG in the S/O nanodispersion skewed the immune response in the allergy model mice toward T helper type 1 immunity, indicating the amelioration of allergic symptoms. This effect was more pronounced when the immunomodulator resiquimod (R-848) was included in the S/O system.